The Degree of Possessing Educational Media Skills by the Students of the University of Jordan - Abu Hilal, Malek M.; Al-Qudah , Mohammad Amin (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to assess the level of Educational Media Skills among students enrolled at the University of Jordan. Methods: The study utilized a quantitative descriptive approach to fulfill its objectives. The study population comprised all undergraduate students enrolled at the University of Jordan in Jordan during the academic year 2022/2023. Using stratification techniques, a sample of 360 male and female students was randomly selected. Data was obtained by administering a questionnaire of 50 items divided into three categories: creating and presenting radio and television programs, photography and video filming, and television directing Results: The results indicate that University of Jordan students perceive their possession of Educational Media Skills to be low overall. Among the different fields assessed, "Preparation and Presentation of Radio and Television Programs" received the highest average score of 1.28, with a standard deviation of 0.57. "TV Direction" followed closely behind, with an average score of 1.23 and a standard deviation of 0.52. Lastly, "Photography and Television Skills" ranked third and last, with an average score of 1.17 and a standard deviation of 0.47. There are notable significant statistical differences at the level of (a = 0.05), associated with the variable of sex, favoring females. There are significant statistical differences at the level of (α=0.05) attributed to college variable in favor of scientific colleges. Conclusions: It concludes that universities should prioritize cultivating media skills among their students, integrating the concepts and dimensions of media into academic courses, and fostering an environment appropriate to achieving this objective.